LAW ENFORCEMENT AGAINST FOREIGN NATIONALS WHO VIOLATE THE LOCAL WISDOM VALUES OF INDIGENOUS PEOPLES (A STUDY OF THE BAYAN TRADITIONAL VILLAGE, MARGA SUB-DISTRICT, TABANAN REGENCY) - Ida Bagus Sudarma (NOTARIIL Jurnal Kenotariatan, 2025)
The existence of customary village communities is recognized in Indonesia as stated in the Constitution. It is known that customary villages have a unique history, process and purpose when compared to written national law. So a thought is needed to combine the existence and application of national law enforcement and customary law. The research method used is empirical legal research, the nature of the research, is descriptive research, the type of data is qualitative and the data source is primary data and secondary data, using data collection methods, observation, interviews, and literature. The technique of determining informants using Non probability sampling, with processing and analyzing the data descriptively qualitative and systematic. Against Foreign Citizens who violate Criminal law in Indonesia, of course, will refer to the enforcement pattern as written criminal law, notwithstanding the imposition of customary sanctions is still carried out with a legal system pattern consisting of substance, structure, and legal culture. This can be considered with the sample of research conducted in Bayan Village, Marga Subdistrict, Tabanan Regency, which applies the customary sanction of Sangaskara Danda against certain mistakes based on local customary law.  Overall, the application of Sangaskara Danda against foreign nationals in Bayan Traditional Village is an example of how local values can be maintained and articulated in a global context, while still prioritizing a fair and educative approach. It should be noted that all forms of customary law enforcement have an orientation towards restoring the situation of local wisdom values that are felt to be degressive to certain behaviors. In order to realize this, it is necessary to coordinate structurally, with the parties involved and have the authority to do so.